Beyond paradise. Series four. - Marshall, Kris; Bretton, Sally; Llewellyn, Dylan; Ahmadi, Zahra (BBC, 2026)
The hit spin-off from Death in Paradise returns, with DI Humphrey Goodman and the Shipton Abbott team facing a fresh wave of mind-boggling crimes. Mystery, humor and heart combine in this popular crime drama series set against the breath-taking landscapes of Devon and Cornwall. Fact and folklore blur when a witness claims a mermaid wrecked a local seaweed farm, while a missing treasure map sparks a hunt for deeply buried truths. Beyond the station, the team face their own personal challenges and newlyweds Humphrey and Martha launch into married life until their houseboat starts taking on water. Can they find a new place to call home? And can Humphrey resolve an impossible dilemma to save his team.